Post-marketing safety re-evaluation of placental peptide injection in China: a large-scale multicenter real-world study - Liguang Duan; Feiyue An; Chen Tian; Wen Yan; Jie Chen; Hongyin Zhang; Xiaoguang Liu; Lingjiao Wang; Zhuo Zhang; Binliang Tong; Chunhua Zhou (Frontiers in Pharmacology)
PurposeThis study conducted a post-marketing safety re-evaluation of placental polypeptide injections in China to support updates to drug guidelines, pharmacovigilance efforts, and rational clinical use, facilitating its inclusion in essential drug lists and medical insurance coverage.MethodsA hospital-based centralized monitoring system tracked 3,000 patients receiving placental polypeptide injections across three medical institutions. Adverse drug reactions (ADRs) and adverse drug events (AEs) were systematically collected and analyzed.ResultsThe mean patient age was 49.65 years, with 96.47% being over 18 years of age. A single dose exceeding 4 mL was administered in 98.34% of the cases, with a median treatment duration of 7 days. Concomitant medication use was high (injectable, 98.43%; non-injectable, 75.43%). One case of vertigo was reported as an ADR in a patient aged >60 years who had melanoma.ConclusionThe ADR rate was 0.03%, confirming the favorable safety profile of placental polypeptide injection. These findings support its safe clinical use and can inform future regulatory and policy decisions.